Development of English Travel Guide for Improving Local Tourism Services in Ollon Valley Tourist Attraction, Tana Toraja - Girik Allo, Markus Deli; Sudarsi, Elim Trika; Taula’bi, Nilma (Journal of Digital Community Services, 2024)
The current tour guides do not meet the needs of local tour guides in the Ollon Valley, so it is necessary to develop travel guides tailored to their needs. Next, the lack of use of technology in the provision of Ollon Valley tour guides, makes it difficult for local tour guides to access up-to-date and accurate information about attractions. And lastly from the aspect of cross-cultural communication, cultural and linguistic differences between local tour guides and foreign tourists can lead to misunderstandings and make the tourist experience less enjoyable, so a better English-speaking travel guide is needed to facilitate better communication between the two parties. In the research on "Development of English Travel Guide for Local Tour Guides in Ollon Valley, Tana Toraja" the method used is the Research and development. The development method is the process used to develop and validate educational products. This method was developed in 10 stages and implemented in Community Service activities Development of English Travel Guides for Local Tour Guides in Remote Areas, Ollon Valley, Tana Toraja. The results confirms that: 1) Local tour guides are in dire need of comprehensive and informative English-speaking tour guides, which not only assist them in providing better service to tourists, but also allow tourists to have a richer and more satisfying experience during their stay in Ollon Valley Attractions, 2) Foreign tourists express a great need for comprehensive information about the attraction, including the history, culture, and activities available in the Ollon valley attraction, and 3) The development of English-language travel guides can improve accessibility for foreign tourists, improve their understanding of attractions, and provide better service.